(untitled) (Architecture Image Studies, 2025)
The study analysed the use of intelligent street lighting systems to improve energy efficiency, safety and aesthetics of urban spaces. The study employed methods for analysing energy consumption, automatic lighting control, assessing visual aesthetics, monitoring light pollution and air quality, and assessing the impact of smart systems on security and public safety. The study showed that the introduction of intelligent street lighting systems significantly improves the energy efficiency of urban lighting through light-emitting diodes (LEDs) and automatic dimming. The analysis showed that the integration of motion and light sensors not only reduces energy consumption but also improves security in public spaces, reducing the number of crimes. The aesthetic design with the ability to change the colour temperature of the light creates a more attractive and comfortable environment, which is confirmed by positive feedback from residents and visitors. In addition, smart lighting systems effectively reduce light pollution by directing light in the right direction and minimising its impact on the night sky. Overall, the study results confirm that smart lighting systems contribute to the sustainable development of urban spaces by improving their functional and visual characteristics. In addition, the study found that smart lighting systems contribute to a significant reduction in maintenance costs due to the long life of LEDs and automatic self-diagnostic functions. The study also determined that such systems improve the visual identification of urban areas, contributing to better navigation and comfortable perception of the urban environment at night.